Penerapan metode pembelajaran terhadap hasil belajar keterampilan pada permainan bulutangkis ditinjau dari persesi kinestetik - Sudiadharma Sudiadharma; Ahmad Rum Bismar; Abdul Rahman (Seminar Nasional LP2M UNM, 2019)
This experimental study aims to compare two learning methods towards the results of learning skills in badminton games. The learning method consists of command learning methods and task learning methods. This study also aims to determine the interaction between learning methods and the ability of kinesthetic perceptions of the results of learning skills in badminton games. The ability of kinesthetic perception consists of high and low. This research was conducted in the Badminton Hall, Faculty of Sport Sciences, Makassar State University, 2016/2017 academic year. The experimental method uses 2x2 treatment by level design. The sample consisted of 40 students divided into four groups, each consisting of 10 students. The data analysis technique was two-way analysis of variance (ANOVA) and continued with the Tukey test at the significance level α = .05. The results of this study indicate that (1). The results of learning skills in badminton games command learning methods are better than task learning methods. (2). There is an interaction between learning methods and the ability of kinesthetic perceptions of the results of learning skills in badminton games. (3). The ability of kinesthetic perception is high, command learning methods are better than task learning methods. (4). The ability of kinesthetic perception is low, the command learning method with the task learning method has no difference.